A geochemical and geophysical reappraisal to the significance of the recent unrest at Campi Flegrei caldera (Southern Italy). (30th March 2017) - Moretti, Roberto; De Natale, Giuseppe; Troise, Claudia
Abstract: Volcanic unrest at calderas involves complex interaction between magma, hydrothermal fluids, and crustal stress and strain. Campi Flegrei caldera (CFc), located in the Naples (Italy) area and characterized by the highest volcanic risk on Earth for the extreme urbanization, undergoes unrest phenomena involving several meters of uplift and intense shallow microseismicity since several decades. Despite unrest episodes display in the last decade only moderate ground deformation and seismicity, current interpretations of geochemical data point to a highly pressurized hydrothermal system. We show that at CFc, the usual assumption of vapor‐liquid coexistence in the fumarole plumes leads to largely overestimated hydrothermal pressures and, accordingly, interpretations of elevated unrest. By relaxing unconstrained geochemical assumptions, we infer an alternative model yielding better agreement between geophysical and geochemical observations. The model reconciles discrepancies between what observed (1) for two decades since the 1982–1984 large unrest, when shallow magma was supplying heat and fluids to the hydrothermal system, and (2) in the last decade. Compared to the 1980's unrest, the post‐2005 phenomena are characterized by much lower aquifers overpressure and magmatic involvement, as indicated by geophysical data and despite large changes in geochemical indicators. Our interpretation points out a model in which shallow sills, intruded during 1969–1984, have completely cooled, so that fumarole emissions are affected now by deeper, CO2 ‐richer, magmatic gases producing the modest heating and overpressure of the hydrothermal system. Our results have important implications on the short‐term eruption hazard assessment and on the best strategies for monitoring and interpreting geochemical data. Plain Language Summary: Campi Flegrei is one of the most dangerous volcanoes on Earth. Last eruption occurred in 1538 but since decades it undergoes unrest phenomena involving ground uplift and seismicity. Geochemical evidences show that current unrest (about 40 cm of uplift since 2005) has different causes to that of 1982–1984, when ground uplift totaled 1.8 m. For many geochemists, the 1982–1984 movement was caused by hydrothermal activity, the degassing magma being deep, and the current activity is caused by shallow magma, but we show that it goes on the contrary. We have checked more than 30 years of geochemical records, and our ongoing interpretation of released gases and physical signals is consistent with current activity being hydrothermal, with the support of very deep magmatic gases, rather than due to the activity of a shallow (3–4 km deep) magma chamber, which instead characterized the 1982–1984 episode. This is only apparently better news, at least for now: activity in which magma is shallow tends to be associated with an increased chance of an eruption, but the change from hydrothermal to magmatic activity can take place at any time. Therefore, a conservative and precautionary attitude and a high level of attention are absolutely necessary. Key Points: New approach to evaluate hydrothermal pressure by considering CH4 reactivity and without assuming steam condensation and redox state ( f O 2 ) Geochemical and geophysical data turn out to be highly coherent in interpreting unrest and the role of shallow and deep magma We identify new strategies for geochemical monitoring (e.g., H2 O/H2 ) of the hydrothermal system and its "heartbeat"